PENGEMBANGAN MODUL PEMBELAJARAN HIDUP SEHAT ANAK USIA DINI PADA TAMAN KANAK-KANAK - Nuria, Ratri (PG-PAUD FKIP Universitas Hamzanwadi, 2018)
: This study aimed to develop a learning module of healthy lifestyle in kindergarten for 5-6 years old. This study includes the development of research that uses methods of research and development (RnD). This procedure of studyÂ uses Borg and Gall model: (1) Step of the beginning study; (2) planning; (3) Developpreliminary form of product;(4) Preliminary field testing;(5)Main product revision; (6) Main field testing;(7) Operational product revision;(8) Operational field testing;(9) Final product revision. Subject that was researched B groub of kindergarten in TK Widya Pura Surakarta, sampling was done random. Instrument to collect data of this research are questionnaires of teacher and questiennaires of student. The data analysis technique used is quantitative descriptive with experiment approach. The result of hypothesis were analysis with t-test paired sample. Validation of module be collect by expert I, expert II, and expert III with developing of step are planning, design, printing. Based on the result has been done can be concluded that the learning module of healthy lifestyle is Effective. Effectiveness of module has collected by calculating the results of field trials to determine differences in the value of field test has been gotten sig. 2 tailed = 0.000 < 0.05 that is signifincance